DNA Methyltransferases: A Novel Target for Prevention and Therapy - Subramaniam, Dharmalingam; Thombre, Ravi; Dhar, Animesh; Anant, Shrikant (Frontiers in Oncology, 2014)
Cancer is the second leading cause of death in US. Despite the emergence of new, targeted agents and the use of various therapeutic combinations, none of the available treatment options are curative in patients with advanced cancer. Epigenetic alterations are increasingly recognized as valuable targets for the development of cancer therapies. DNA methylation at the 5-position of cytosine, catalyzed by DNA methyltransferases (DNMTs), is the predominant epigenetic modification in mammals. DNMT1, the major enzyme responsible for maintenance of the DNA methylation pattern is located at the replication fork and methylates newly biosynthesized DNA. DNMT2, the smallest mammalian DNMT is believed to participate in the recognition of DNA damage, DNA recombination and mutation repair. It is composed solely of the C-terminal domain, and does not possess the regulatory N-terminal region. The levels of DNMTs, especially those of DNMT3B, DNMT3A, and DNMT3L are often increased in various cancer tissues and cell lines, which may partially account for the hypermethylation of promoter CpG-rich regions of tumor suppressor genes in a variety of malignancies. Moreover, DNMT1 functions in self-renewal and maintenance of cancer stem cell in several cancers. Inhibition of DNMTs has demonstrated reduction in tumor formation in part through the increased expression of tumor suppressor genes. Hence, DNMTs can potentially be used as anticancer agents. Dietary phytochemicals also inhibit DNMTs and cancer stem cells; this represent a promising approach for the prevention and treatment of many cancers.